ACCUMULATION HISTORY OF ANTHROPOGENIC HEAVY METALS (CU, ZN, AND PB) IN MASAN BAY SEDIMENTS, SOUTHEASTERN KOREA: A ROLE OF CHEMICAL FRONT IN THE WATER COLUMN - Jeong K.S.; Cho J.H.; Lee J.H.; Kim K.H. (My University, 2006)
In Masan Bay, the drainage basin for the wastewater of heavily-industrialized cities and harbors in the southeastern Korea, a composite analysis of sediment cores reveals that accumulation history and behaviors of heavy metals are distinctive depending on anthropogenic activities and dissolved oxygen in water column. In the inner bay, Cu, Zn, and Pb have been enriched, associated with organic and sulfide matter, over background levels since the mid-1940s. It seems to result from the deposition of stream-disposed sewage under a poor water circulation before most of sewage collected in Masan City has been treated and disposed through an outfall into the outer bay since the late 1993. The outfall disposal contaminated the topmost sediments of the outer bay with the three metals, 2.2 to 3.2 times as much as the background. The three metals are strongly associated with Mn in the bay mouth, probably resulting from their oxidative precipitation beneath a chemical front of water column that forms by expansion and mixing of anoxic bay bottom water with oxygenated coastal water. The bay sediments seem to act as a mobile pool in that Mn and the pollutant metals are often remobilized to the anoxic bottom water in summer.
Keywords: MASAN BAY; SEDIMENT CORES; ACCUMULATION HISTORY; POLLUTANT METALS; ANTHROPOGENIC ACTIVITIES; CHEMICAL FRONT